Assessment ofopen-ended questions directed to prospective science teachers in terms of scientific creativity - ŞAHİN, FATMA (ELSEVIER SCIENCE BV, 2014)
Innovation is mandatory for development in every part of social life. In knowledge societies, education's role is not to re-create society, but to create new society (Baykal, 2003). Scientific knowledge is partially product of imagination and creativity (Khishfe and Abd-El-Khalick, 2002). Creative thinking is posing different and unique ideas for any situation or problem in daily lives and generating multidirectional solutions, combination of cases, concepts and objects by relating them to each other and construct new experiences, differing from paths that everybody is accustomed to (Temizkan, 2011; Oznacar and Bildiren, 2012). Creativity involves both scientificity and daily life (Farooq, 2008). As a matter of fact, problem solving, constructing hypothesis and experiment and technical innovation require specific form of scientific creativity (Lin, Hu, Adey and Shen, 2003). According to Kocabas (1993), scientific creativity can be defined as motivation for scientific research, formularization of knowledge and research problems, constructing a general domain for solution of a scientific question, research ability appropriate to causes and similarities, patience and resistance for a detailed research.The purpose of the study is to assess prospective science teachers' answers to open-ended questions in terms of scientific creativity. For this purpose, prospective science teachers were asked 3 open-ended questions. The data gathered from the study were examined in terms of fluency, flexibility, originality and scientific knowledge which are the features of scientific creativity and expert validity was established. Qualitative data gathered from the study was also presented as numbered quantitative data and they were discussed comparatively within. Prospective science teachers' scientific creativity assessments were made according to the findings of the study and some related recommendations were presented about scientific creativity skills. (C) 2014 The Authors. Published by Elsevier Ltd.
Keywords: scientific creativity; creativity; prospective teachers